If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 18 + -2g Solving 24 = 18 + -2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '2g' to each side of the equation. 24 + 2g = 18 + -2g + 2g Combine like terms: -2g + 2g = 0 24 + 2g = 18 + 0 24 + 2g = 18 Add '-24' to each side of the equation. 24 + -24 + 2g = 18 + -24 Combine like terms: 24 + -24 = 0 0 + 2g = 18 + -24 2g = 18 + -24 Combine like terms: 18 + -24 = -6 2g = -6 Divide each side by '2'. g = -3 Simplifying g = -3
| t^2-6t-11=0 | | 44-4h=12 | | 2+4x=-16 | | x=(x+1)(x+3) | | 91-x=171 | | x=x+1x+3 | | x^2+8ix-16=0 | | 166=4(x+20) | | 75n+30=375 | | 2x+4x=2x+36 | | (3x-5)+x+201=125 | | 12(x-7)=26-2 | | (3x-5)x+201=125 | | z^2+zw+w^2=0 | | z^2-2zw+w^2=0 | | -4(x-6)=-10 | | x^2-ix+6=0 | | -2(x+3)=-2 | | 2(p+10)=4 | | 81y^3-16y=0 | | 6(m-6)=5 | | 9y^3-4y^2=0 | | 2(7h-8)=-18 | | 3(x+6)=-10 | | -26=2k+4k | | 105-5x=9x-23 | | 3(1-7d)=33 | | 3(n-5)=14 | | 6(5+4r)=25 | | -4(9x-7)= | | -4aaa+2aaa-6aaa= | | (xxxxxxx)7= |